Pseudomyopathic Changes in Needle Electromyography in Lambert-Eaton Myasthenic Syndrome - Teppei Komatsu; Kota Bokuda; Toshio Shimizu; Tetsuo Komori; Reiji Koide (Case Reports in Neurological Medicine)
Lambert-Eaton myasthenic syndrome (LEMS) is a rare presynaptic disorder of the neuromuscular junction in association with cancer and subsequently in cases in which no neoplasm has been detected (O’Neill et al., 1988). The diagnosis of LEMS is based on the combination of fluctuating muscle weakness, diminished or absent reflexes, and a more than 60% increment of compound muscle action potential (CMAP) amplitude after brief exercise or 50 Hz stimulation for 1 s in a repetitive nerve stimulation (RNS) test (Oh et al., 2005). On the other hand, needle electromyography (EMG) findings related to LEMS have not been well described. Here, we report a case of LEMS, which showed apparent myopathic changes in needle EMG findings. Furthermore, we retrospectively examined the needle EMG findings in 8 patients with LEMS. In six of the 8 patients, the EMG findings showed myopathy-like findings. Although the findings of needle EMG indicated myopathic changes at a glance, the motor unit potential (MUP) returned to normal after a sustained strong muscle contraction. We propose the name “pseudomyopathic changes” for this phenomenon.